Generation of two RNF2 homozygous knockout human embryonic stem cell lines by CRISPR/Cas9 system - Shan, Yongli; Ma, Lishi; Zhang, Cong; Zhang, Yanqi; Zhang, Jingyuan; Xiao, Lu; Wei, Yanxing; Yu, Yanhong (Stem cell research, 2020)
Human RNF2 (RING1B) gene is a critical epigenetic modification factor for embryonic development, pluripotency and differentiation of embryonic stem cells (ESCs). To further gain insights into the role of RNF2 in cell fate decisions of human ESCs, here we generated two RNF2 homozygous knockout human ESC lines by CRISPR/Cas9 genome editing technology. These cell lines maintained a normal karyotype and typical undifferentiated state in terms of morphology, pluripotent gene expression, and had differentiation potential in vivo. These cell lines provide good cell resources to explore the role of RNF2 gene in embryonic development and lineage differentiation in vitro.